The Staff Nurse Clinical Leader at the Bedside: Swedish Registered Nurses’ Perceptions - Inga E. Larsson; Monika J. M. Sahlsten (Nursing Research and Practice)
Registered nurses at the bedside are accountable for and oversee completion of patient care as well as directly leading and managing the provision of safe patient care. These nurses have an informal leadership role that is not associated with any given position. Leadership is a complex and multifaceted concept and its meaning is unclear, especially in the staff nurse context. The aim was to describe registered nurses’ perceptions of what it entails to be the leader at the bedside in inpatient physical care. A phenomenographic approach was employed. Interviews were performed with Swedish registered nurses (n=15). Five descriptive categories were identified: demonstrating clinical knowledge, establishing a good atmosphere of collaboration, consciously structuring the work in order to ensure patients’ best possible nursing care, customized presence in the practical work with patients according to predetermined prerequisites, and monitoring coworkers’ professional practice. Registered nurses informal role as leader necessitates a social process of deliberate effort to attain and maintain leader status and authority. Participants used deliberate communicative approaches and interactive procedures. Leader principles grounded in the core values of the nursing profession that ensure nursing values and person-centered attributes were a key aspect.